TADLIS MERUSAK PRINSIP ’ANTARADHIN DALAM TRANSAKSI - Taufiq Taufiq (JURIS (Jurnal Ilmiah Syariah), 2017)
One of the principles emphasized in transaction is willingness (antaradhin). The principle ensures that all parties involved in transaction get satisfaction. This means none of the parties get benefit while the other suffers from loss as the consequences of the transaction. The jumhur ulama agree that the principle is implementing in the form of ijab and qabul.  The principle of antaradhin is achieved through sharing the same amount necessary information (complete information) between two parties. However, not all of transactions end in satisfaction. This is due to the fact that one of the parties tries to hide necessary information from the other one. That means one party is deceived by the other. This kind of behavior is known as cheating (tadlis). Tadlis  may appear in the form of hiding real or true conditions of the trading goods, increasing the price and so forth. These may take hiding information on the quality, quantity, time, and price of the goods. This paper therefore aims at discussing in more detailed Islamic perceptions toward antaradhin (willingness), tadlis (deception) and how the habit of committing to tadlis destroys the principles of  antaradhin in the process transaction.Kata kunci: tadlis, ‘antaradhin, transaksi